2011
DOI: 10.1063/1.3658848
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic limit to photonic-plasmonic light-trapping in thin films on metals

Abstract: We calculate the maximum optical absorptance enhancements in thin semiconductor films on metals due to structures that diffuse light and couple it to surface plasmon polaritons. The calculations can be used to estimate plasmonic effects on light-trapping in solar cells. The calculations are based on the statistical distribution of energy in the electromagnetic modes of the structure, which include surface plasmon polariton modes at the metal interface as well as the trapped waveguide modes in the film. The enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 25 publications
0
53
0
Order By: Relevance
“…Despite the early work suggesting that the absorption enhancement in thin slabs is less than 4n 2 , recent work has shown that the enhancement may in fact exceed this limit through the use of photonic crystals, 5 plasmonic waveguides, 6 and high index claddings, 7,8 which all elevate the local density of optical states to achieve enhancment. 9 Here we revisit the case of a thin waveguide and determine that the 4n 2 limit can be exceeded for a number of structures that support large propagation constants and/or slow modal group velocities.…”
Section: Limit In Thin Waveguidesmentioning
confidence: 99%
“…Despite the early work suggesting that the absorption enhancement in thin slabs is less than 4n 2 , recent work has shown that the enhancement may in fact exceed this limit through the use of photonic crystals, 5 plasmonic waveguides, 6 and high index claddings, 7,8 which all elevate the local density of optical states to achieve enhancment. 9 Here we revisit the case of a thin waveguide and determine that the 4n 2 limit can be exceeded for a number of structures that support large propagation constants and/or slow modal group velocities.…”
Section: Limit In Thin Waveguidesmentioning
confidence: 99%
“…The calculation of the modal material loss rate has also been used to understand the effect of plasmonic loss in solar cell light trapping schemes [19]. However, only a few recent papers have attempted to understand the general behavior of loss in plasmonic systems from a purely analytic perspective.…”
mentioning
confidence: 99%
“…Propagating plasmons are not expected in random structures which may instead support localized plasmons [11][12][13] at the location of the nanoparticles. These plasmons can lead to optical losses, unless localized plasmons re-radiate into photon modes [14].…”
Section: Introductionmentioning
confidence: 96%